Green Place Implementation on Raja Kacang Hijau Home Industry in Tebing Tinggi City - Daniel Collyn; Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Murbanto Sinaga (Budapest International Research and Critics University, 2023)
This study aims to analyze the green place implementation on Raja Kacang Hijau home industry. This research is a qualitative descriptive study. The type of data used is primary data. The data were obtained through field observations and interviews conducted with the business owner of Raja Kacang Hijau. Data analysis techniques include data reduction, data presentation and drawing conclusions. In this study, a gap analysis will also be carried out to see the suitability of green place implementation in Raja Kacang Hijau. The results of the analysis show that the green place concept has been applied to the business of Raja Kacang Hijau. The implementation has not been maximized so that improvements are needed in the future. Business owners have a high awareness of the importance of preserving the environment and providing quality products, namely green products for consumers. Raja Kacang Hijau already has green marketing SOPs, in this case green places, implemented according to SOPs, but not consistent and incomplete documentation. This shows that Raja Kacang Hijau implements sales, marketing and distribution of products that prioritize environmental elements (green distribution) and energy saving (green store).